2013
DOI: 10.1037/a0033219
|View full text |Cite
|
Sign up to set email alerts
|

Reduced autobiographical memory specificity as an emotional avoidance strategy in opioid-dependent patients.

Abstract: This study investigates the reduced specificity of autobiographical memories in opioid-dependent patients and examines whether this phenomenon corresponds to an avoidance strategy in opioiddependent patients and among the general population. Thirty opioid-dependent patients and 30 control participants were given Williams' and Scott's Autobiographical Memory Test (AMT) to evaluate the level of memory specificity. The use of cognitive avoidance strategy was measured with the Cognitive Avoidance Questionnaire (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
2
8
0
1
Order By: Relevance
“…Concerning the lack of specificity of the memories, this result is consistent with the observation of Cuervo‐Lombard and colleagues () in recently detoxified AUD patients and in studies using cue words to initiate the recall of memories (e.g., using the Autobiographical Memory Test) both in individuals with AUD (D'Argembeau et al., ; Whiteley et al., ) or with other substance addictions (Gandolphe and Nandrino, ; Gandolphe et al., ). Whatever the method used, the results showed that patients with AUD overgeneralized their AM, including SDM.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Concerning the lack of specificity of the memories, this result is consistent with the observation of Cuervo‐Lombard and colleagues () in recently detoxified AUD patients and in studies using cue words to initiate the recall of memories (e.g., using the Autobiographical Memory Test) both in individuals with AUD (D'Argembeau et al., ; Whiteley et al., ) or with other substance addictions (Gandolphe and Nandrino, ; Gandolphe et al., ). Whatever the method used, the results showed that patients with AUD overgeneralized their AM, including SDM.…”
Section: Discussionsupporting
confidence: 85%
“…First, D'Argembeau and colleagues () and Whiteley and colleagues () showed that nonamnesic patients with AUD reported more general memories than specific memories. As described in other autobiographical models (Conway, ; Conway and Pleydell‐Pearce, ; Kopelman, ), this defect in AM specificity highlights the fact that as in other forms of addiction (Gandolphe et al., ; Nandrino et al., ), AUD patients have difficulty in accessing the specific perceptual and emotional material of AM. However, this phenomenon was not observed in AUD patients who had been abstinent for a longer period (6 months), whereas it was present in recently detoxified ones (Poncin et al., ).…”
supporting
confidence: 53%
“…A partire dallo studio appena citato, altre ricerche hanno confermato l'esistenza di una tendenza a richiamare ricordi categoriali e non ricordi specifici -definita ipergeneralizzazione della memoria (overgeneral memory) -come tratto (vale a dire condizione stabile) associato in particolare a depressione e stress post traumatico (McNally et al, 1995;Moore e Zoellern, 2007;Soderlund et al, 2014), ma anche, pur essendo la letteratura meno consolidata al riguardo, disturbi alimentari (Dalgleish et al, 2007), disturbo borderline di personalità (Startup et al, 2001) e abuso di sostanze (Gandolphe et al, 2013).…”
Section: La Specificità Della Memoria Autobiograficaunclassified
“…In this sense, several research teams have highlighted an increasing number of general autobiographical events among alcohol dependent [10][11][12], opiates users [13][14][15] and cannabis users [16].…”
Section: Introductionmentioning
confidence: 99%